Class VII Members’ Actions Of Thankfulness And Gratitude In The Legend Of Heroes Trail Of Cold Steel Video Game - Akmal Dafa Hizbullah; Kusuma Wijaya; Rommel Utungga Pasopati (PT. Gudang Pustaka Cendekia, 2025)
This study explores the concept of gratitude, specifically focusing on the Action of Thankfulness expressed by Class VII members in The Legend of Heroes: Trails of Cold Steel video game. Using the Find-Remind-Bind theory by Sara B. Algoe, the study identifies expressions of gratitude that reinforce social bonds among characters. The qualitative analysis of in-game dialogues and interactions reveals that thankfulness manifests in various forms, such as verbal appreciation, acknowledgment of contributions, and reinforcement of interpersonal relationships. This study highlights how gratitude influences character development and strengthens emotional connections within the narrative. In conclusion, this research contributes to the study of digital drama and psychology of literature in video game by showing how psychological elements, especially action of thankfulness, can be analyzed through interactive narratives.